Distribution of Polyphenolic and Isoprenoid Compounds and Biological Activity Differences between in the Fruit Skin + Pulp, Seeds, and Leaves of New Biotypes of Elaeagnusmultiflora Thunb - Sabina Lachowicz-Wiśniewska; Ireneusz Kapusta; Carla M. Stinco; Antonio J. Meléndez-Martínez; Anna Bieniek; Ireneusz Ochmian; Zygmunt Gil (MDPI AG, 2021)
The purpose of this study was to determine the distribution of polyphenolic and isoprenoid compounds and organic acids in the fruit skin + pulp, seeds, and leaves of six new biotypes of Elaeagnus multiflora Thunb., as well as their in vitro biological potency. The polyphenols and isoprenoids were determined with UPLC-PDA-MS/MS (ultra-performance liquid chromatography coupled to photodiode array detection and electrospray ionization tandem mass spectrometry) and RRLC-MS/MS (rapid resolution liquid chromatography/tandem mass spectrometry) methods, the organic acid with HPLC-RID (high-performance liquid chromatography coupled to a Refractive Index Detector), and the antioxidant capacity using ABTS and FRAP assays. Enzymatic activity was established as the ability to inhibit α-amylase, α-glucosidase, and pancreatic lipase. Owing to such an effective technique, 88 compounds were recorded, with 17 polyphenolic compounds and 3 isoprenoids identified for the first time in the seeds and leaves of cherry silverberry. In total, 55 compounds were identified in the leaves, 36 in the seeds, and 31 in the fruit skin + pulp. The predominant polyphenol was polymeric procyanidin (66-95% of total polyphenolics), whereas the predominant isoprenoids were chlorophyll b and (all-E)-lycopene. The results of our work noted that there are significant differences in the profiles of several secondary metabolites between the analyzed parts of the plant, and depending on the need, the compounds can be used to develop different innovative food or cosmetic products.